Looking backwards and forwards: tracking and persistence of weight status between early childhood and adolescence - Hayes, Alison J; Carrello, Joseph P; Kelly, Patrick J; Killedar, Anagha; Baur, Louise A (My University, 2021)
ackground/objective Many studies have shown that child BMI or weight status tracks over time, but the demographic predictors of high tracking have not been investigated. Our objective was to identify demographic predictors of persistence (duration) of healthy weight and overweight/obesity throughout childhood, and to examine whether tracking was age dependent. Methods We conducted secondary data analysis of 4606 children from the Birth cohort and 4983 children from the Kindergarten cohort of the Longitudinal Study of Australian Children with follow-up to age 12/13 and 16/17 years, respectively. Retrospective and prospective tracking were examined descriptively. Time-to-event analysis determined demographic predictors of persistence of healthy weight and overweight/obesity beyond age 4–5 years, after controlling for child BMI z-score. Weight status was determined using WHO methods. Results Tracking of healthy weight was consistently higher than that of overweight/obesity, and incident overweight was equally likely throughout childhood and adolescence. Tracking of overweight was lower for children under 7 years than in middle childhood and adolescence (2-year probability 65%, compared with 80%; 2-year resolution of overweight 35 and 20%). Children of lower socioeconomic position, those from culturally and linguistically diverse backgrounds, and girls were more likely to move into overweight (hazard ratios [95%CI] for incident overweight: 1.39 [1.26–1.52], 1.16 [1.02–1.31] and 1.12 [1.02–1.23], respectively) and less likely to resolve their overweight (hazard ratios for resolution of overweight/obesity: 0.77 [0.69–0.85], 0.8 [0.69–0.92] and 0.79 [0.71–0.81], respectively) during childhood. However, persistence of weight status was not significantly affected by rurality or Indigenous status (P > 0.05). Conclusions Lowest tracking and highest natural resolution of overweight in children under 7 years suggests this may be an opportune time for interventions to reduce overweight. Primary and secondary prevention programmes during the school years should be designed with special consideration for lower socioeconomic communities, for culturally and linguistically diverse populations and for girls.
International Journal of Obesity
Keywords: Adolescents and youth; Health and wellbeing